Robot Compatible Environment and Conditions - V. Farkas, Zita; Nádas, Gergely; Kolossa, József; Korondi, Péter (Periodica Polytechnica Civil Engineering, 2021)
Service robot technology is progressing at a fast pace. Accurate robot-friendly indoor localization and harmonization of built environ-ment in alignment with digital, physical, and social environment becomes emphasized. This paper proposes the novel approach of Robot Compatible Environment (RCE) within the architectural space. Evolution of service robotics in connection with civil engineering and architecture is discussed, whereas optimum performance is to be achieved based on robots’ capabilities and spatial affordances. For ubiquitous and safe human-robot interaction, robots are to be integrated into the living environment. The aim of the research is to highlight solutions for various interconnected challenges within the built environment. Our goal is to reach findings on comparison of robotic and accessibility standards, synthesis of navigation, access to information and social acceptance. Checklists, recommendations, and design process are introduced within the RCE framework, proposing a holistic approach.